2020
DOI: 10.14202/vetworld.2020.1280-1287
|View full text |Cite
|
Sign up to set email alerts
|

A topical ointment formulation containing leaves' powder of Lawsonia inermis accelerate excision wound healing in Wistar rats

Abstract: Aim: Lawsonia inermis (LI), a naturally grown or cultivated shrub in Northeast of Africa and India, has been traditionally used as a strong remedy for several injuries. However, few studies have reported its use as a cicatrizing agent. The aim of this study was to evaluate the effect of daily application of an ointment prepared with LI leaves' powder on wound healing in Wistar rats. Materials and Methods: Twenty female Wistar rats were used in this study. Excisional wound model was realized by removin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The use of traditional medicinal plants for wound healing is based on their antiseptic, astringent, anti-inflammatory, and antimicrobial properties [ 37 ]. This antimicrobial activity is related to facilitating the wound healing process, since open wounds are particularly prone to infections, especially by bacteria, and they also provide an entry point for systemic infections [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of traditional medicinal plants for wound healing is based on their antiseptic, astringent, anti-inflammatory, and antimicrobial properties [ 37 ]. This antimicrobial activity is related to facilitating the wound healing process, since open wounds are particularly prone to infections, especially by bacteria, and they also provide an entry point for systemic infections [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation or individual utilization of He had significant positive impacts in wound's contraction and epithelialization in rats. He has treasures from bioactive compounds, which could contribute to healing processes of wounded skins; the combined synergistic actions of multiple He constituents are assumed to correlate with its curative beneficial effects [35]. The He phytoconstituents include phenolic amalgams (e.g., coumarins, naphthalenes, lignans, alkylphenones, xanthones, naphthoquinones, tannins, and flavonoids), alkaloids, terpenes, and steroids [28,29,34].…”
Section: Microbicidal Action the Consequences Of Exposure Tomentioning
confidence: 99%
“…Additionally, the He flavonoids could augment skin WH via multiple actions, e.g., their antibacterial, astringent, cell necrosis prevention, cytokine expression modulation during inflammation, angiogenesis improvement, and prostaglandin synthesis inhibition [25,29,33,70]. The He tannins' contents were also documented for contributing to WH through enhancing tissue organization and regeneration; the He tannin actions mainly depend on their astringent, antioxidant, antibacterial, anti-inflammatory, and free radical biochelation activities [28,34,35,72]; these actions frequently lead to stimulate keratinocyte/fibroblast proliferation, improve WH and angiogenesis, and develop rapid crust via proteins' precipitation in damaged tissue [29,30,35]. The He-loaded nanopolymers, e.g., PLA and gelatin nanofibers, showed additional capabilities for controlling wound infections and WH via formation of hygienic dressings [37].…”
Section: Microbicidal Action the Consequences Of Exposure Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological studies on Lawsonia inermis revealed antibacterial activity [6,7], antifungal [8,9], antiparasitic [10,11], molluscicidal [12], antioxidant [13,14], hepatoprotective [15,16], central nervous [17], analgesic [18,19], anti-inflammatory [20,21], antipyretic [18], wound [22,23] and burn healing [24], immuno-modulatory [25,26], anti-urolithiatic [27,28], antidiabetic and hypolipidemic [29,30], antiulcer [31], antidiarrhoeal [19] , diuretic [32], anticancer [33,34] and many other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%